Building sound insulation material based on nano material modification and preparation method thereof

By using highly branched additives and composite foaming agents to form a porous structure in sound insulation materials for buildings, the problem of nanoparticle agglomeration is solved, and the uniform dispersion and stable bonding of nanoparticles are achieved, thereby improving the sound insulation and mechanical properties of the material.

CN121379045APending Publication Date: 2026-01-23SHANDONG SHIBOGE SPECIAL RUBBER & PLASTIC MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511820094.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-04
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Nanoparticles in existing building sound insulation materials are prone to agglomeration, resulting in uneven dispersion of fillers and poor sound absorption.

Method used

The high branching degree of the additives provides molecular-level steric hindrance, and the nanoparticles and additives form bivalent bonds for in-situ anchoring. Combined with the composite foaming agent, a uniform porous structure is formed, and a continuous sound energy conduction and dissipation channel is constructed, thereby improving the dispersion uniformity of nanoparticles and the mechanical properties of the material.

Benefits of technology

It significantly improves the sound absorption effect and mechanical properties of sound insulation materials, achieves uniform dispersion and stable bonding of nanoparticles, and enhances the sound insulation and mechanical properties of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121379045A_ABST
    Figure CN121379045A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to a building sound insulation material based on nano material modification. Comprising the following raw materials in parts by weight: 30-50 parts of matrix resin, 8-15 parts of composite filler, 5-10 parts of a composite foaming agent, 4-8 parts of a curing agent, 3-8 parts of a fiber reinforcement, 3-6 parts of an epoxy toughening agent, 3-6 parts of a coupling agent, 2-5 parts of a plasticizer, 1-4 parts of a flame retardant, 0.5-2 parts of an antioxidant and 0.5-2 parts of a curing accelerator. According to the invention, by solving the problem of agglomeration of nanoparticles, uniform dispersion of carbon nanotubes and nano-silica is realized, the uniformly dispersed carbon nanotubes construct a continuous sound energy conduction dissipation channel by virtue of a high length-diameter ratio, incident sound energy is converted into heat energy through multiple reflections and friction, and the nano-silica cooperates with the composite foaming agent to form a uniform porous structure, so that the sound energy can be converted into heat energy. Sound energy transmission is further blocked, and the sound insulation performance is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, specifically to a sound insulation material for buildings modified with nanomaterials and its preparation method. Background Technology

[0002] Building sound insulation materials are a class of functional building materials that control the propagation of noise inside and outside buildings by blocking, absorbing or dissipating sound energy. They are widely used in building components such as walls, floors, doors and windows, and elevator shafts. They are one of the core materials for ensuring the sound environment quality of residential, office and public spaces. Among them, nanomaterial modification technology can precisely control the microstructure of materials and improve their comprehensive performance, which is a key research direction for the upgrading of sound insulation materials.

[0003] In existing technologies, when nanomaterials are added to sound insulation materials, the nanoparticles, due to their extremely high surface energy, are prone to migration and aggregation, resulting in uneven dispersion of the filler and poor sound absorption. Therefore, this invention provides a sound insulation material for buildings modified with nanomaterials and its preparation method. Summary of the Invention

[0004] The purpose of this invention is to provide a sound insulation material for buildings modified with nanomaterials and its preparation method. The sound insulation material for buildings modified with nanomaterials prepared by this invention not only has good sound insulation performance, but also excellent compressive strength, effectively improving the performance of the sound insulation material.

[0005] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a sound insulation material for buildings modified with nanomaterials, comprising the following raw materials in parts by weight: 30-50 parts matrix resin, 8-15 parts composite filler, 5-10 parts composite foaming agent, 4-8 parts curing agent, 3-8 parts fiber reinforcement, 3-6 parts epoxy toughening agent, 3-6 parts coupling agent, 2-5 parts plasticizer, 1-4 parts flame retardant, 0.5-2 parts antioxidant and 0.5-2 parts curing accelerator.

[0006] Furthermore, the composite filler is prepared from a composite dispersion and additives.

[0007] Furthermore, the additive is prepared from ethylenediamine and methyl methacrylate.

[0008] Furthermore, the ethylenediamine is pretreated before the preparation of the additive.

[0009] Furthermore, the fiber reinforcement is pretreated before the preparation of the building sound insulation material modified with nanomaterials.

[0010] Further, the preparation method of the composite filler is as follows: the additive is added to the composite dispersion at a mass ratio of 1:(11-12), the temperature is raised to 60-70℃ and kept at that temperature for 3-4 hours to obtain a precursor. A silane coupling agent is added to the precursor, the temperature is kept at 80℃ for 2 hours, and the mixture is vacuum filtered at a vacuum degree of -0.095MPa. The filter residue is vacuum dried at 80℃ to constant weight, then ground at 300rpm for 30 minutes and passed through a 200-mesh sieve to obtain the composite filler. The silane coupling agent is KH-560, and the amount of silane coupling agent is 2.5-3% of the mass of the composite dispersion.

[0011] Further, the preparation method of the composite dispersion is as follows: carbon nanotubes are added to anhydrous ethanol at a solid-liquid ratio of 1:(8-12), and ultrasonically dispersed at a power of 400W and a frequency of 20kHz for 40min to obtain a suspension. Tetraethyl orthosilicate is added to the suspension, the pH is adjusted to 4-5 with acetic acid, and the mixture is kept at 50℃ for 1-2h to obtain the composite dispersion. The mass of tetraethyl orthosilicate is 2-4 times the mass of carbon nanotubes.

[0012] Further, the preparation method of the additive is as follows: pretreated ethylenediamine is added to a three-necked flask, nitrogen gas is purged at a flow rate of 40 mL / min for protection, the temperature is raised to 60-70℃, methyl methacrylate is added dropwise at a rate of 1 drop per second, the reaction is maintained at this temperature for 2-3 hours, the temperature is raised to 80℃, a water separator is connected and maintained at this temperature for 2-3 hours, and the mixture is cooled to room temperature to obtain an intermediate reactant. Glycidol is added to the intermediate reactant and the mixture is maintained at 70℃ for 4 hours to obtain the additive. The mass ratio of ethylenediamine to methyl methacrylate is 1:(4-4.5), and the mass ratio of ethylenediamine to glycidol is 1:(2-3).

[0013] Further, the pretreatment method of the ethylenediamine is as follows: ethylenediamine is placed in a low-temperature plasma reactor, vacuumed to 2-4 Pa, ammonia gas is introduced at a flow rate of 25 mL / min, and plasma treatment is performed at a power of 60 W for 10-20 min. Then, diethylenetriamine is added, and the mixture is stirred at 300 rpm and 40-60 °C for 1 h to obtain pretreated ethylenediamine, wherein the mass of diethylenetriamine is 8-12% of the mass of ethylenediamine.

[0014] Furthermore, the pretreatment method of the fiber reinforcement is as follows: the fiber reinforcement is placed in a plasma reactor, the vacuum is drawn to 5Pa, nitrogen gas is introduced at a flow rate of 30-40mL / min, the treatment is carried out at a power of 80W for 8-15min, and then sealed and stored. The fiber reinforcement is glass fiber with a length of 3-5mm.

[0015] Furthermore, the matrix resin is bisphenol A epoxy resin E44.

[0016] Furthermore, the composite foaming agent is prepared by mixing azodicarbonamide and sodium bicarbonate at a mass ratio of 3:1.

[0017] Furthermore, the curing agent is diethylenetriamine, the epoxy toughening agent is carboxyl-terminated nitrile butadiene rubber, the coupling agent is silane coupling agent KH-550, the plasticizer is dioctyl phthalate, the flame retardant is magnesium hydroxide, the antioxidant is antioxidant 1010, and the curing accelerator is 2-methylimidazole.

[0018] Secondly, the present invention provides a sound insulation material for buildings based on nanomaterial modification, comprising the following steps: S1: Place the composite foaming agent in a vacuum drying oven and dry it at 60℃ for 2-3 hours to obtain the dried composite foaming agent. Seal it for later use. S2: Add the matrix resin to the internal mixer and pre-melt it at 100-120℃ and 50rpm for 8-10 minutes to obtain the molten resin matrix; S3: Add composite filler, epoxy toughening agent and plasticizer to the molten resin matrix, heat to 130-140℃, adjust the speed to 150rpm, mix and stir for 10-20min to obtain resin mixture, add coupling agent, flame retardant and antioxidant to resin mixture, stir at 120℃ and 120rpm for 5-10min, cool to 80-90℃, add curing accelerator and stir for 3min, then add drying composite foaming agent, pretreated fiber reinforcement and curing agent, stir rapidly for 5-10min to obtain mixed slurry; S4: Pour the mixed slurry into a mold preheated to 80℃, hot press it at 150℃ and 5MPa, keep it warm and pressurized for 30-50 minutes, and then let it cool naturally to below 60℃ to demold, thus obtaining a building sound insulation material modified with nanomaterials.

[0019] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, the high branching degree of the additive provides sufficient molecular-level steric hindrance, and the bicovalent bond between the nanoparticles and the additive anchors them in situ, solving the problem of nanoparticle aggregation and achieving uniform dispersion of carbon nanotubes and nano-silica. The uniformly dispersed carbon nanotubes, with their high aspect ratio, construct a continuous sound energy conduction and dissipation channel, allowing the incident sound energy to be dispersed through multiple reflections, thus significantly improving the sound absorption effect. At the same time, the uniform porous structure formed by nano-silica and the composite foaming agent further blocks the propagation of sound energy. The synergistic effect of the components significantly improves the sound insulation performance.

[0020] 2. In this invention, the silane coupling agent on the outer layer of the composite filler can form stable covalent bonds with the hydroxyl groups of the epoxy resin through an addition reaction, avoiding the low mechanical transfer efficiency caused by weak bonding. The glass fiber surface treated by plasma is etched to form a rough texture and introduces a large number of hydroxyl groups, which can not only form hydrogen bonds and chemical bonds with the epoxy resin matrix, but also form multi-point anchoring with the uniformly dispersed nano-modified filler, efficiently transferring mechanical loads and improving the mechanical properties of the material. Attached Figure Description

[0021] Figure 1 The present invention provides a flowchart of a sound insulation material for buildings based on nanomaterial modification and its preparation method. Detailed Implementation

[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0023] It should be noted that the raw materials used in the following embodiments are all commercially available.

[0024] Example 1: Prepare the following raw materials by weight: 30 parts matrix resin, 8 parts composite filler, 5 parts composite foaming agent, 4 parts curing agent, 3 parts fiber reinforcement, 3 parts epoxy toughening agent, 3 parts coupling agent, 2 parts plasticizer, 1 part flame retardant, 0.5 parts antioxidant and 0.5 parts curing accelerator.

[0025] Pretreated ethylenediamine: Ethylenediamine was placed in a low-temperature plasma reactor, evacuated to 2 Pa, and ammonia gas was introduced at a flow rate of 25 mL / min. The plasma was treated with 60 W for 10 min. Then, diethylenetriamine was added and stirred at 300 rpm and 40 °C for 1 h to obtain pretreated ethylenediamine, wherein the mass of diethylenetriamine was 8% of the mass of ethylenediamine.

[0026] Preparation of additive: Pretreated ethylenediamine was added to a three-necked flask, and nitrogen gas was purged at a flow rate of 40 mL / min for protection. The temperature was raised to 60 °C, and methyl methacrylate was added dropwise at a rate of 1 drop per second. The reaction was maintained at this temperature for 2 h, then the temperature was raised to 80 °C, and a water separator was connected to maintain the temperature for 2 h. The mixture was then cooled to room temperature to obtain an intermediate reactant. Glycidol was added to the intermediate reactant, and the mixture was maintained at 70 °C for 4 h to obtain the additive. The mass ratio of ethylenediamine to methyl methacrylate was 1:4, and the mass ratio of ethylenediamine to glycidol was 1:2.

[0027] Preparation of composite dispersion: Carbon nanotubes were added to anhydrous ethanol at a solid-liquid ratio of 1:8 and ultrasonically dispersed at a power of 400W and a frequency of 20kHz for 40 minutes to obtain a suspension. Tetraethyl orthosilicate was added to the suspension, and the pH was adjusted to 4 with acetic acid. The mixture was kept at 50℃ for 1 hour to obtain a composite dispersion. The mass of tetraethyl orthosilicate was twice the mass of carbon nanotubes.

[0028] Preparation of composite filler: Add the additive to the composite dispersion at a mass ratio of 1:11, heat to 60℃ and keep warm for 3 hours to obtain the precursor. Add silane coupling agent to the precursor, keep warm at 80℃ for 2 hours, vacuum filter at a vacuum degree of -0.095MPa, dry the filter residue at 80℃ to constant weight, grind at 300rpm for 30 minutes, and pass through a 200-mesh sieve to obtain the composite filler. The silane coupling agent is KH-560, and the amount of silane coupling agent is 2.5% of the mass of the composite dispersion.

[0029] Pre-treatment of fiber reinforcement: The fiber reinforcement was placed in a plasma reactor, evacuated to 5 Pa, and nitrogen gas was introduced at a flow rate of 30 mL / min. After treatment at 80 W for 8 min, it was sealed and stored. The fiber reinforcement was glass fiber with a length of 3 mm.

[0030] Preparation of composite foaming agent: Azodicarbonamide and sodium bicarbonate are mixed at a mass ratio of 3:1.

[0031] Preparation of sound insulation materials for buildings based on nanomaterial modification: S1: Place the composite foaming agent in a vacuum drying oven and dry it at 60°C for 2 hours to obtain the dried composite foaming agent. Seal it for later use. S2: Add the matrix resin to the internal mixer and pre-melt it at 100°C and 50 rpm for 8 minutes to obtain the molten resin matrix; S3: Add composite filler, epoxy toughening agent and plasticizer to the molten resin matrix, heat to 130℃, adjust the speed to 150rpm, mix and stir for 10min to obtain resin mixture, add coupling agent, flame retardant and antioxidant to resin mixture, stir for 5min at 120℃ and 120rpm, cool to 80℃, add curing accelerator and stir for 3min, then add drying composite foaming agent, pretreated fiber reinforcement and curing agent, stir rapidly for 5min to obtain mixed slurry; S4: Pour the mixed slurry into a mold preheated to 80°C, hot press it at 150°C and 5MPa, keep it warm and pressurized for 30 minutes, and then let it cool naturally to below 60°C to demold, thus obtaining a sound insulation material for buildings modified with nanomaterials.

[0032] Example 2:

[0033] Prepare the following raw materials by weight: 40 parts matrix resin, 12 parts composite filler, 8 parts composite foaming agent, 6 parts curing agent, 5 parts fiber reinforcement, 4 parts epoxy toughening agent, 4 parts coupling agent, 3 parts plasticizer, 2.5 parts flame retardant, 1 part antioxidant and 1 part curing accelerator.

[0034] Pretreated ethylenediamine: Ethylenediamine was placed in a low-temperature plasma reactor, evacuated to 3 Pa, and ammonia gas was introduced at a flow rate of 25 mL / min. The plasma was treated with 60 W for 15 min. Then, diethylenetriamine was added and stirred at 300 rpm and 50 °C for 1 h to obtain pretreated ethylenediamine, wherein the mass of diethylenetriamine was 10% of the mass of ethylenediamine.

[0035] Preparation of additive: Pretreated ethylenediamine was added to a three-necked flask, and nitrogen gas was purged at a flow rate of 40 mL / min for protection. The temperature was raised to 65 °C, and methyl methacrylate was added dropwise at a rate of 1 drop per second. The reaction was maintained at this temperature for 2.5 h. The temperature was then raised to 80 °C, and a water separator was connected to maintain the temperature for 2.5 h. The mixture was cooled to room temperature to obtain an intermediate reactant. Glycerol was added to the intermediate reactant, and the mixture was maintained at 70 °C for 4 h to obtain the additive. The mass ratio of ethylenediamine to methyl methacrylate was 1:4.2, and the mass ratio of ethylenediamine to glycerol was 1:2.5.

[0036] Preparation of composite dispersion: Carbon nanotubes were added to anhydrous ethanol at a solid-liquid ratio of 1:10 and ultrasonically dispersed at a power of 400W and a frequency of 20kHz for 40 minutes to obtain a suspension. Tetraethyl orthosilicate was added to the suspension, and the pH was adjusted to 4.5 with acetic acid. The mixture was kept at 50℃ for 1.5 hours to obtain a composite dispersion. The mass of tetraethyl orthosilicate was 3 times the mass of carbon nanotubes.

[0037] Preparation of composite filler: Additives were added to the composite dispersion at a mass ratio of 1:11.5, and the mixture was heated to 65℃ and kept at that temperature for 3.5 h to obtain a precursor. Silane coupling agent was added to the precursor, and the mixture was kept at 80℃ for 2 h. Vacuum filtration was performed at a vacuum degree of -0.095 MPa. The filter residue was dried at 80℃ under vacuum until constant weight, then ground at 300 rpm for 30 min and passed through a 200-mesh sieve to obtain the composite filler. The silane coupling agent was KH-560, and the amount of silane coupling agent was 2.8% of the mass of the composite dispersion.

[0038] Pre-treatment of fiber reinforcement: The fiber reinforcement was placed in a plasma reactor, evacuated to 5 Pa, and nitrogen gas was introduced at a flow rate of 35 mL / min. After treatment at a power of 80 W for 12 min, it was sealed and stored. The fiber reinforcement was glass fiber with a length of 4 mm.

[0039] Preparation of composite foaming agent: Azodicarbonamide and sodium bicarbonate are mixed at a mass ratio of 3:1.

[0040] Preparation of sound insulation materials for buildings based on nanomaterial modification: S1: Place the composite foaming agent in a vacuum drying oven and dry at 60°C for 2.5 hours to obtain the dried composite foaming agent, then seal it for later use. S2: Add the matrix resin to a mixer and pre-melt it at 110°C and 50rpm for 9 minutes to obtain a molten resin matrix; S3: Add composite filler, epoxy toughening agent and plasticizer to molten resin matrix, heat to 135℃, adjust speed to 150rpm, mix and stir for 15min to obtain resin mixture, add coupling agent, flame retardant and antioxidant to resin mixture, stir for 8min at 120℃ and 120rpm, cool to 85℃, add curing accelerator and stir for 3min, then add dry composite foaming agent, pretreated fiber reinforcement and curing agent, stir rapidly for 8min to obtain mixed slurry; S4: Pour the mixed slurry into a mold preheated to 80°C, hot press it at 150°C and 5MPa, keep it warm and pressurized for 40 minutes, and then let it cool naturally to below 60°C to demold, thus obtaining a sound insulation material for buildings modified with nanomaterials.

[0041] Example 3: Prepare the following raw materials by weight: 50 parts matrix resin, 15 parts composite filler, 10 parts composite foaming agent, 8 parts curing agent, 8 parts fiber reinforcement, 6 parts epoxy toughening agent, 6 parts coupling agent, 5 parts plasticizer, 4 parts flame retardant, 2 parts antioxidant and 2 parts curing accelerator.

[0042] Pretreated ethylenediamine: Ethylenediamine was placed in a low-temperature plasma reactor, evacuated to 4 Pa, and ammonia gas was introduced at a flow rate of 25 mL / min. The plasma was treated with 60 W for 20 min. Then, diethylenetriamine was added and stirred at 300 rpm and 60 °C for 1 h to obtain pretreated ethylenediamine, wherein the mass of diethylenetriamine was 12% of the mass of ethylenediamine.

[0043] Preparation of additive: Pretreated ethylenediamine was added to a three-necked flask, and nitrogen gas was purged at a flow rate of 40 mL / min for protection. The temperature was raised to 70 °C, and methyl methacrylate was added dropwise at a rate of 1 drop per second. The reaction was maintained at this temperature for 3 h, then the temperature was raised to 80 °C, and a water separator was connected to maintain the temperature for 3 h. The mixture was then cooled to room temperature to obtain an intermediate reactant. Glycidol was added to the intermediate reactant, and the mixture was maintained at 70 °C for 4 h to obtain the additive. The mass ratio of ethylenediamine to methyl methacrylate was 1:4.5, and the mass ratio of ethylenediamine to glycidol was 1:3.

[0044] Preparation of composite dispersion: Carbon nanotubes were added to anhydrous ethanol at a solid-liquid ratio of 1:12 and ultrasonically dispersed at a power of 400W and a frequency of 20kHz for 40 minutes to obtain a suspension. Tetraethyl orthosilicate was added to the suspension, and the pH was adjusted to 5 with acetic acid. The mixture was kept at 50℃ for 2 hours to obtain a composite dispersion. The mass of tetraethyl orthosilicate was 4 times the mass of carbon nanotubes.

[0045] Preparation of composite filler: Add the additive to the composite dispersion at a mass ratio of 1:12, heat to 70℃ and keep warm for 4 hours to obtain the precursor. Add silane coupling agent to the precursor, keep warm at 80℃ for 2 hours, vacuum filter at a vacuum degree of -0.095MPa, dry the filter residue at 80℃ to constant weight, grind at 300rpm for 30 minutes, and pass through a 200-mesh sieve to obtain the composite filler. The silane coupling agent is KH-560, and the amount of silane coupling agent is 3% of the mass of the composite dispersion.

[0046] Pre-treatment of fiber reinforcement: The fiber reinforcement is placed in a plasma reactor, evacuated to 5 Pa, and nitrogen is introduced at a flow rate of 40 mL / min. After treatment at 80 W for 15 min, it is sealed and stored. The fiber reinforcement is glass fiber with a length of 5 mm.

[0047] Preparation of composite foaming agent: Azodicarbonamide and sodium bicarbonate are mixed at a mass ratio of 3:1.

[0048] Preparation of sound insulation materials for buildings based on nanomaterial modification: S1: Place the composite foaming agent in a vacuum drying oven and dry it at 60°C for 3 hours to obtain the dried composite foaming agent. Seal it for later use. S2: Add the matrix resin to the internal mixer and pre-melt it for 10 minutes at 120°C and 50 rpm to obtain the molten resin matrix; S3: Add composite filler, epoxy toughening agent and plasticizer to molten resin matrix, heat to 140℃, adjust speed to 150rpm, mix and stir for 20min to obtain resin mixture, add coupling agent, flame retardant and antioxidant to resin mixture, stir for 10min at 120℃ and 120rpm, cool to 90℃, add curing accelerator and stir for 3min, then add drying composite foaming agent, pretreated fiber reinforcement and curing agent, stir rapidly for 10min to obtain mixed slurry; S4: Pour the mixed slurry into a mold preheated to 80°C, hot press it at 150°C and 5MPa, keep it warm and pressurized for 50 minutes, and then let it cool naturally to below 60°C to demold, thus obtaining a sound insulation material for buildings modified with nanomaterials.

[0049] Comparative Example 1: The difference between this comparative example and Example 1 is that nano-silica is used instead of composite filler in this comparative example.

[0050] Comparative Example 2 differs from Example 1 in that it does not contain fiber reinforcement.

[0051] Comparative Example 3 differs from Example 1 in that the ethylenediamine in this comparative example is not pretreated.

[0052] Performance testing: The performance of the building sound insulation materials modified with nanomaterials prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the test data are recorded in the table below: Table 1

[0053] In the performance test, the sound insulation performance test was conducted in accordance with GB / T 19889.3-2005, and the mechanical performance was reflected by impact toughness. The test was conducted in accordance with GB / T 2567-2021. The impact toughness test used an unnotched specimen with an impact energy of 15J and the average value of 5 tests was taken.

[0054] The sound insulation performance test results of the building sound insulation materials modified with nanomaterials prepared in Examples 1-3 and Comparative Examples 1-3 were 53.9dB, 54.6dB, 55.2dB, 42.6dB, 50.1dB, and 46.9dB, respectively.

[0055] The mechanical properties of the nanomaterial-modified sound insulation materials for buildings prepared in Examples 1-3 and Comparative Examples 1-3 were 14.2 kJ / m², 15.5 kJ / m², 16.1 kJ / m², 9.6 kJ / m², 5.8 kJ / m², and 11.4 kJ / m², respectively.

[0056] It is evident that the sound insulation and mechanical properties of the nanomaterial-modified building sound insulation materials after treatment in Comparative Examples 1-3 are lower than those in Examples 1-3. This indicates that the additives in the composite filler provide molecular-level steric hindrance through their highly branched three-dimensional configuration, and the active sites of the pretreated ethylenediamine promote the formation of bivalent bonds between the matrix and nanoparticles, inhibiting the aggregation of carbon nanotubes and nano-silica. The uniformly dispersed carbon nanotubes construct a continuous three-dimensional sound energy conduction and dissipation channel, allowing the incident sound energy to diffuse through multiple reflections. Meanwhile, the nano-silica strengthens the mechanical substrate through rigid support. At the same time, the outer layer of the silane coupling agent undergoes a precise chemical reaction with the hydroxyl groups of the epoxy resin, constructing a stable chemical bonding interface between the filler and the resin, and enhancing the interface load transfer efficiency. Therefore, in Comparative Example 1, the single nano-silica lacks these synergistic effects and cannot simultaneously achieve improved sound insulation performance and enhanced mechanical interface, resulting in a significant performance degradation. Pretreatment of ethylenediamine generates active free radicals through plasma etching, which, combined with the amino grafting of diethylenetriamine, can significantly increase the number of active sites on the ethylenediamine surface, thereby greatly improving the branching degree of the subsequently synthesized branched matrix. Higher branching degree can provide nanoparticles with more sufficient molecular-level steric hindrance and anchoring points, which is the basis for ensuring the dispersion stability and interfacial bonding of fillers. In contrast, the branching degree of the branched matrix in Comparative Example 3 is insufficient, the tendency of nanoparticle aggregation increases, and the interfacial bonding is weakened, resulting in a certain degree of reduction in sound insulation and mechanical properties. Plasma etching creates a rough texture on the fiber surface and introduces active groups such as hydroxyl and carboxyl groups. This enhances the hydrogen and covalent bonding with the epoxy resin and forms multi-point anchoring with the uniformly dispersed composite filler, achieving efficient transfer and dispersion of mechanical loads and effectively improving the material's impact toughness. At the same time, the macroscopic interwoven structure of the fibers can help the composite foaming agent form a more uniform porous distribution, indirectly optimizing the sound insulation effect. Without fiber reinforcement, the impact toughness decreases significantly because the mechanical load cannot be effectively dispersed without fiber reinforcement, making the material prone to fracture due to local stress concentration. Furthermore, the uniformity of the porous structure decreases, resulting in a certain degree of reduction in sound insulation effect.

[0057] By comparing and analyzing the relevant data in the table, it can be seen that the building sound insulation material based on nanomaterial modification prepared by this invention not only has good sound insulation performance but also excellent mechanical properties. This indicates that the building sound insulation material based on nanomaterial modification provided by this invention has a broader market prospect and is more suitable for widespread application.

[0058] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0059] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A sound insulation material for buildings based on nanomaterial modification, characterized in that, The raw materials include the following parts by weight: 30-50 parts matrix resin, 8-15 parts composite filler, 5-10 parts composite foaming agent, 4-8 parts curing agent, 3-8 parts fiber reinforcement, 3-6 parts epoxy toughening agent, 3-6 parts coupling agent, 2-5 parts plasticizer, 1-4 parts flame retardant, 0.5-2 parts antioxidant and 0.5-2 parts curing accelerator; The composite filler is prepared from a composite dispersion and additives; The additive is prepared from ethylenediamine and methyl methacrylate; The ethylenediamine is pretreated before the preparation of the additive; The fiber reinforcement is pretreated before the preparation of building sound insulation materials modified with nanomaterials.

2. The building sound insulation material based on nanomaterial modification according to claim 1, characterized in that, The composite filler is prepared as follows: the additive is added to the composite dispersion at a mass ratio of 1:(11-12), the temperature is raised to 60-70℃ and kept at that temperature for 3-4 hours to obtain a precursor. A silane coupling agent is added to the precursor, the temperature is kept at 80℃ for 2 hours, and the mixture is vacuum filtered at a vacuum degree of -0.095MPa. The filter residue is dried at 80℃ under vacuum until constant weight, then ground at 300rpm for 30 minutes and passed through a 200-mesh sieve to obtain the composite filler. The silane coupling agent is KH-560, and the amount of silane coupling agent is 2.5-3% of the mass of the composite dispersion.

3. The building sound insulation material based on nanomaterial modification according to claim 1, characterized in that, The composite dispersion is prepared as follows: carbon nanotubes are added to anhydrous ethanol at a solid-liquid ratio of 1:(8-12), and ultrasonically dispersed at a power of 400W and a frequency of 20kHz for 40 minutes to obtain a suspension. Tetraethyl orthosilicate is added to the suspension, and the pH is adjusted to 4-5 with acetic acid. The mixture is kept at 50℃ for 1-2 hours to obtain the composite dispersion. The mass of tetraethyl orthosilicate is 2-4 times the mass of carbon nanotubes.

4. The building sound insulation material based on nanomaterial modification according to claim 1, characterized in that, The additive is prepared as follows: pretreated ethylenediamine is added to a three-necked flask, nitrogen gas is purged at a flow rate of 40 mL / min for protection, the temperature is raised to 60-70℃, methyl methacrylate is added dropwise at a rate of 1 drop per second, the reaction is maintained at this temperature for 2-3 hours, the temperature is raised to 80℃, a water separator is connected and maintained at this temperature for 2-3 hours, and the mixture is cooled to room temperature to obtain an intermediate reactant. Glycidol is added to the intermediate reactant and the mixture is maintained at 70℃ for 4 hours to obtain the additive. The mass ratio of ethylenediamine to methyl methacrylate is 1:(4-4.5), and the mass ratio of ethylenediamine to glycidol is 1:(2-3).

5. The building sound insulation material based on nanomaterial modification according to claim 1, characterized in that, The pretreatment method for ethylenediamine is as follows: Ethylenediamine is placed in a low-temperature plasma reactor, evacuated to 2-4 Pa, ammonia gas is introduced at a flow rate of 25 mL / min, and plasma treatment is performed at a power of 60 W for 10-20 min. Then, diethylenetriamine is added, and the mixture is stirred at 300 rpm and 40-60 °C for 1 h to obtain pretreated ethylenediamine, wherein the mass of diethylenetriamine is 8-12% of the mass of ethylenediamine.

6. The building sound insulation material based on nanomaterial modification according to claim 1, characterized in that, The pretreatment method of the fiber reinforcement is as follows: the fiber reinforcement is placed in a plasma reactor, the vacuum is drawn to 5Pa, nitrogen gas is introduced at a flow rate of 30-40mL / min, the treatment is carried out at a power of 80W for 8-15min, and then sealed and stored. The fiber reinforcement is glass fiber with a length of 3-5mm.

7. The building sound insulation material based on nanomaterial modification according to claim 1, characterized in that, The matrix resin is bisphenol A epoxy resin E44.

8. The building sound insulation material based on nanomaterial modification according to claim 1, characterized in that, The composite foaming agent is prepared by mixing azodicarbonamide and sodium bicarbonate at a mass ratio of 3:

1.

9. The building sound insulation material based on nanomaterial modification according to claim 1, characterized in that, The curing agent is diethylenetriamine, the epoxy toughening agent is carboxyl-terminated nitrile butadiene rubber, the coupling agent is silane coupling agent KH-550, the plasticizer is dioctyl phthalate, the flame retardant is magnesium hydroxide, the antioxidant is antioxidant 1010, and the curing accelerator is 2-methylimidazole.

10. The building sound insulation material based on nanomaterial modification according to claim 1, characterized in that, Includes the following steps: S1: Place the composite foaming agent in a vacuum drying oven and dry it at 60℃ for 2-3 hours to obtain the dried composite foaming agent. Seal it for later use. S2: Add the matrix resin to the internal mixer and pre-melt it at 100-120℃ and 50rpm for 8-10 minutes to obtain the molten resin matrix; S3: Add composite filler, epoxy toughening agent and plasticizer to the molten resin matrix, heat to 130-140℃, adjust the speed to 150rpm, mix and stir for 10-20min to obtain resin mixture, add coupling agent, flame retardant and antioxidant to resin mixture, stir at 120℃ and 120rpm for 5-10min, cool to 80-90℃, add curing accelerator and stir for 3min, then add drying composite foaming agent, pretreated fiber reinforcement and curing agent, stir rapidly for 5-10min to obtain mixed slurry; S4: Pour the mixed slurry into a mold preheated to 80℃, hot press it at 150℃ and 5MPa, keep it warm and pressurized for 30-50 minutes, and then let it cool naturally to below 60℃ to demold, thus obtaining a building sound insulation material modified with nanomaterials.

Citation Information

Cited By

  • Synergistic flame-retardant epoxy resin-based porous sound insulation composite material and application thereof

    CN122080587A